Jewellery bulky hinge bracelet / Siti Sarah Ahmad Tajalli Alyamany - Ahmad Tajalli Alyamany, Siti Sarah (2022)
Malaysian Traditional Batik was the inspiration for this jewellery bracelet. The identity of Malaysians is intrinsically rooted in batik. Through ideation and idea development, a motif from a batik sarong was used as the inspired for this jewellery creation. All women require jewellery. Then, keep it maintained.